3D Geological Modeling in Mineral Deposits (Copper Ore Body Cases) - Bele, Sirelda (European Scientific Journal, ESJ, 2018)
Munella’s deposit is one of the most important mineral deposits of Albania. It is rich in mineral resources such as copper, zinc, gold, etc. For this reason Geological 3D modeling is very important because it gives detailed information on management in the most optimal way to mine. In this article, 3D modeling of copper bodies was carried out through modeling software using the implicit method. This method uses advanced algorithms that are Polyharmonic Radial Basis Functions (RBF) generates the best surface area of the ore that can have some Z values and can perfectly customize the incomplete surfaces by utilizing 211 drilling data. The ore bodies that are created with this method are divided into blocks that represent the distribution of copper in%. The results achieved in this study provide an accurate overview of the most important sources of deposits and major concentrations of copper for the efficient management and exploitation of the mine.